Seasonal variation in plasma hormone/metabolite concentrations in fleeceweight-selected and control Romney rams : a thesis presented in partial fulfillment of the requirements for the degree of Masters of Agricultural Science in Animal Science at Massey University - Matthew, Tessa Corine (Massey University, 1990)
In New Zealand, sheep related products provide a substantial contribution to the national economy. Traditionally, the national economy has been influenced by the fluctuating prices of both meat and wool in world markets. New Zealand is the second largest wool producer in the world and it is the dominant coarse wool producer, accounting for approximately 45 per cent of world production and 70 per cent of all internationally traded coarse wools {Anon, 1989). Of the various wool characteristics which determine returns to the farmer, production per head is probably the most important (Wickham and McPherson, 1985). By world standards, the average production of wool by New Zealand sheep is high. The national clip average is 5.5 kg per head and the lambing percentage is just under 100 per cent (Anon, 1989) despite relatively low labour inputs into New Zealand flocks. It is important for each individual farmer, as well as New Zealand as a whole, to maintain a high position in the world market and, in order to do this, ways have to be found to increase the gains made from the production of wool. One method by which per head production may be increased is through genetic selection. Currently in New Zealand, rams are selected as two tooths (i.e. approximately 15 months of age), using measurements such as their own greasy fleece weight, and possibly that of their relatives, as indicators of superior wool production. Total fleeceweight is calculated for each ram and is sometimes adjusted for non-genetic factors such as date of birth, birth rank (i.e. single or twin), body weight and maternal age. Once these factors have been taken account of, those rams with the best adjusted fleeceweights are selected and used as sires. Those rams not chosen, due to their lower production figures, are culled.
Keywords: Sheep; Genetics; Breeding; Wool; Romney Marsh sheep